Numerical simulation of gas–liquid flow behavior in the nozzle exit region of an effervescent atomizer. (January 2019) - Sun, Chunhua; Ning, Zhi; Qiao, Xinqi; Lv, Ming; Fu, Juan; Zhao, Jin; Wang, Xintao
The pressure drop and particular geometric structure of the nozzle exit region of an effervescent atomizer cause complex changes in the flow pattern, which could affect the spray performance. In this study, the gas–liquid two-phase flow behavior in the nozzle exit region of the effervescent atomizer was investigated numerically. The results show that the flow behaviors in the nozzle exit region have disparate characteristics with different upstream flow regimes. For upstream churn flow, the liquid film morphology is closely related to fluctuation in the gas–liquid velocity, and the flow parameters (fluids' velocities and gas void fraction) at the exit section vary regularly with time. For upstream bubbly flow, the instantaneous gas void fraction is determined by the bubble distribution inside the mixing chamber. The bubble will form a tadpole-like shape as a result of the complex flow field and the surface tension. The flow parameters at the exit section are in an oscillatory decay, and the fluctuation amplitude is larger than for churn flow. For upstream slug flow, the gas void fraction varies significantly with time. The discrete characteristic of the gas–liquid flow parameters at exit section is very obvious.